Secondary glaucoma after paediatric cataract surgery. Issue 12 (2nd May 2007) - Swamy, B N; Billson, F; Martin, F; Donaldson, C; Hing, S; Jamieson, R; Grigg, J; Smith, J E H
Abstract : Aim: To determine the prevalence and risk factors associated with secondary glaucoma postcongenital cataract surgery. Methods: All children diagnosed as having congenital cataracts in a major children's hospital between 1985 and 2005 were included in a retrospective case series. Medical records of 423 eyes among 283 patients who underwent cataract surgery with or without intraocular lens implantation at age ⩽16 for congenital cataract were reviewed. The main outcome measure was presence or absence of secondary glaucoma and time to glaucoma postsurgery. The following risk factors were evaluated: age at cataract surgery, presence of systemic anomalies, microcornea, persistent hyperplastic primary vitreous (PHPV), primary capsulotomy/anterior vitrectomy, primary intraocular lens implantation, secondary membrane surgery and duration of postoperative observation. Results: The statistical methods were the use of Kaplan–Meier survival analysis and Multivariate Cox hazards regression analysis. The mean follow-up was 6.3 (SD 5.0) years (median 4.6 years; range 0.5 to 20.3 years). Glaucoma developed in 36 of 234 patients (15.4%). Multivariate Cox proportional hazards regression analysis identified age less than 9 months at time of surgery (RR 2.9, 95% CI 1.3 to 7.7; p = 0.03), microcornea (RR 3.7, 95% CI 2.0 to 7.0; p<0.001), and follow-up time as important predictors of glaucoma. PHPV (RR 1.4, 95% CI 0.7 to 2.7; p = 0.41) and primary posterior capsulotomy/anterior vitrectomy (RR 2.2, 95% CI 0.9 to 5.5; p = 0.17) were not significantly associated with secondary glaucoma in the multivariate model. The mean time to glaucoma after congenital cataract surgery was 4.9 years (range 2 weeks to 16.8 years). Conclusion: Secondary glaucoma is an important sequela in patients who undergo surgery for congenital cataracts. It is imperative that these patients get lifelong surveillance, as glaucoma can occur years after the initial operation.